Effect of iron impurity in liquid phase exfoliated tungsten disulfide based ultraviolet heterojunction photodetector - Ahmad, Harith; Thandavan, Tamil Many K. (American Scientific Publishers, 2018)
Photoconductivity characteristics of iron (Fe) impurity in a tungsten disulfide (WS2) based ultraviolet (UV) heterojunction photodetector are and presented On: Wed,inin WS impurities through electrolysis process during current–voltage (I–V) characterizationis found the2 sample by field emission scanning electron microscopy (FESEM) and energy dispersive X-ray (EDX) analysis Unexpectedly, this Fe impurity enhances the performance of the WS2 based UV heterojunction photodetector due to the increase of the electron concentration in the WS2 structural matrix. Photon responsivity is observed to increase by 231% while the dark current reduces by 80% as compared to pure WS2 samples. The highest responsivity achieved is 5.9 AW−1 when the input optical power is 7.8 μW at 382 nm with a bias voltage of 10 V and a dark current as low as 6 μA. The enhancement due to the Fe impurities will encourage additional studies into the doping and hybridization of metals into two dimensional (2D) materials for better photodetector performance.